Eclogarum in libros historicos Veteris Testamenti epitome Teil 2: der Exoduskommentar - Prokopios von Gaza 465-529 (Die griechischen christlichen Schriftsteller der ersten Jahrhunderte, 2020)
From the great commentary on the first historical books of the Old Testament (CPG 7430) by Procopius of Gaza (465/470-526/530), this volume includes the commentary on the book of exodus, published for the first time in the complete Greek text. Alongside Procopius' continuous text is hidden a collection of excerpts from works whose original versions have been lost, including by Origen and Didymus the Blind